Delizioso Truck / Azizan Azni Zainuddin ... [et. al] - Zainuddin, Azizan Azni; Richmond Allan, Emily Abigail; Awang Razak, Dayang Nurjazmina Hazirah; Azam, Afif Azhar; Mohamad Shukry, Nurul Nabilah (2017)
Our business is named 'Delizioso Truck'. The word 'delizioso' itself means yummy in Italian. Our food truck will be operating next to TM Point Mukah. We are doing partnership business which consisted of five members. Azizan Azni Bin Zainudin as our general manager and admin manager. He will help the other managers in managing the business. Besides that, he also is going to manage the administration plan. The second member of the partnership is Emily Abigail Richmond Allan who is in charge of marketing plan. She will be taking the position as a Marketing Manager. She's the sleeping partner in our group and have our other members covered up for her. The next members in our partnership are Afif Azhar Bin Azam and Dayang Nurjazmina Hazirah Binti Awang Razak. They will both be taking the position as Operation Managers. They will arange the operation included in this business. This is such as usage of raw materials, the process chart. Capacity planning, remuneration and the business layout and others. Lastly, Nurul Nabilah Binti Mohamad Shukry is the Financial Manager in our business plan. She manage and organizes the cash flow, balance sheet and other financial activities in this business.